Understanding the role of visuals in commercial website interaction on smartphone display - Achmad Syarief; Nedina Sari; Amanda Amelia (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2021)
Flexible and ease of internet access through mobile device in Indonesia has changed the way users interact with commercial websites, especially online ticketing service website. Yet, no study on how the presented website visuals on smartphone display perceived and experienced by users is found. This paper exposes users’ interactive experience on smartphone display, showcasing 3 (three) popular online ticketing service providers in Indonesia, traveloka dot com, pegi-pegi dot com, and tiket dot com. 60 individuals were purposively sampled and each was asked to access all chosen websites using provided smartphone. 2 (two) pages follow-up questionnaire was presented to each respondent: first page is for identifying users’ perception 5 (five) items likert-scale responses and second page is for identifying users’ experiences using Schrepp, Hinderks & Thomaschewski’s UXQ (User Experience Questionnaire). Results show that when interacting with online ticketing service websites on smartphone, sites that look simple and easy to interact with may provide sense of savvyness, comfortability, and security. This indicates that presented website visuals on smartphone display affect users’ experience when using online services. Although further studies are needed, this results offer valuable insights to the discussions of human interactive experience in using online platform.